Realist review of policy intervention studies aimed at reducing exposures to environmental hazards in the United States. (December 2016) - Apollonio, Dorie; Wolfe, Nicole; Bero, Lisa
Abstract Background Exposure to pollution is a significant risk to human health. However few studies have attempted to identify the types of policy interventions that can reduce the health risks of pollution exposure in the United States. The study objective was to conduct a realist review of policy interventions conducted or aimed at reducing chemical exposures in humans or the environment where exposure was measured. Methods A systematic literature search identified published articles that assessed policy interventions using exposure data. Two coders independently extracted data from the studies, assessing methods, context, details of interventions, outcomes, and risks of bias. Data were analyzed iteratively and manually to identify the most effective and transferrable types of interventions. The reasons for variability in the success of different interventions were explored. Results The review found that regulatory interventions that eliminate point sources of pollution appeared to reduce exposure to environmental hazards. Regular monitoring to provide environmental and human exposure data helped assess compliance with the regulatory standards. Educational and economic interventions were less successful. Conclusions Although some types of regulatory interventions appear to reduce exposures, our findings are limited by the nature of existing interventions, the weaknesses of the study designs used in the literature, and the lack of details on implementation. Information on contextual factors that influence implementation would assist with future reviews and could help identify effective interventions.